2022
DOI: 10.4018/ijthi.299075
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Drivers of Self-Service Technology (SST) Satisfaction and Marketing Bottom Lines

Abstract: Whilst self-service technologies (SSTs) are novel and evolving, they have rapidly grown popular across various retail service settings. Having been introduced into the Nigerian banking space, the level of customers’ satisfaction from the system is still unknown given that it has disrupted the initial service setup customers were used to. Utilising two theoretical perspectives, this study examined what drives customers’ satisfaction with banks’ SST and further assesses their influence on different marketing bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Immediately after its introduction, the technology acceptance model has been widely used, and has received empirical support from many studies. Some studies have also confirmed that its predictive ability in information technology use behavior is higher than that of planned behavior theory ( Mathieson, 1991), and subsequent studies Research applies it to self-service technology (Ugwuanyi et al, 2022;Hassan & Farmanesh, 2022;Chow, Yeow & See, 2022). Therefore, this study will use the technology acceptance model to explore the attitudes and behavioral intentions of medical consumers using medical self-service technology.…”
Section: Issn: 2706-6606 Introductionmentioning
confidence: 84%
“…Immediately after its introduction, the technology acceptance model has been widely used, and has received empirical support from many studies. Some studies have also confirmed that its predictive ability in information technology use behavior is higher than that of planned behavior theory ( Mathieson, 1991), and subsequent studies Research applies it to self-service technology (Ugwuanyi et al, 2022;Hassan & Farmanesh, 2022;Chow, Yeow & See, 2022). Therefore, this study will use the technology acceptance model to explore the attitudes and behavioral intentions of medical consumers using medical self-service technology.…”
Section: Issn: 2706-6606 Introductionmentioning
confidence: 84%